La Sala del Crimen de la Real Audiencia de México: construcción y conflictos jurisdiccionales durante los siglos XVI y XVII - Hernández Santiago, Oscar (História do Direito, 2022)
This article analyzes the construction process of the Sala del Crimen’s jurisdiction in the Real Audiencia de Mexico during the XVI and XVII centuries. Moreover, it studies some of its internal and external problems with other jurisdictions. It takes in consideration as sources the legal records and statute law.